Malignant transformation rate of oral leukoplakia: A meta analysis - P Ramaswamy; Ch Sai Kiran; B Mrudula Raju; Munipati Swathi Kiranmai (Wolters Kluwer Medknow Publications, 2020)
Background: Oral squamous cell carcinoma is the most common form of head and neck cancer which is sometimes preceded by potentially malignant disorders such as leukoplakia. Oral leukoplakia is a potentially malignant lesion that has been considered to confer increased risk for the development of oral cancer. Tobacco smoking and alcohol intake have been attributed as major risk factors. Many articles were published connecting the malignant transformation rate to lifestyle modifications. As contemporary sources of information regarding malignant transformation rate of oral leukoplakia are lacking, there is a need to have a comprehensive evaluation of leukoplakia and its malignant transformation potential. Aim: This study aims to provide a systematic review of research on the current malignant transformation rate of oral leukoplakia. Objective: To find association between malignant transformation rate and other parameters in oral leukoplakia. Results: The malignant transformation rate of oral leukoplakia was observed to be 5.7% from the year 1963 and has increased by two-fold from year 1996 to 10.9%. Malignant transformation rate of verrucous leukoplakia was 28.2%. Dysplastic malignant transformation rate of leukoplakia was 53.7% [95% Confidential interval: 32.9%, 74.5%] overall malignant transformation rate of oral leukoplakia was 10.9%. Conclusion: The two-fold increase in the malignant transformation rate since 1990s should be considered as an alarming issue, and necessary steps have to be taken in this regard.